Exploring Transitivity System Used in Students’ Recount Texts at Islamic Boarding School - Zaenal Novianto; Sidik Indra Nugraha; Kelik Wachyudi (Edumaspul: Jurnal Pendidikan, 2022)
The main objectives of this research are to explore the types of transitivity process used by tenth grade students in writing recount text at one of the Islamic Boarding Schools in Karawang and to describe the pedagogical implication of the use of transitivity analysis. This research employed qualitative approach to analyze the transitivity process of students' writing recount texts. The data in this research are five students’ recount texts. Five recount texts written by the students were purposively selected as the research data, and were then analyzed in accordance with SFL theory (elaborated in Eggins, 2004). The result showed that there are six types of process found in the students’ recount texts, i.e. material process, relational, mental, verbal, existential, and behavioral. The material process appeared in the data the most frequently, with a total number of appearances 60 (70%) times. Additionally, inappropriate grammar was also found in the texts. This showed that transitivity analysis could also detect grammar in clauses in detail. Thus, two essential implications can be drawn from this research: (1) Transitivity system offers an alternative technique for teachers to analyze the students’ recount texts based on functional linguistic lens, and (2) transitivity system provides detailed arrangement of ways English recount text are developed.